Links between Adolescent Athletes' Prosocial Behavior and Relationship with Parents: A Mixed Methods Study - Aušra Lisinskienė; Marc Lochbaum (MDPI AG, 2018)
Adolescent relationships with parents are of the highest importance. The relationships likely reflect the nature of internal working models in youth sport that may well function as a psychological template during the construction of youth prosocial behavior. However, researchers' focus to date has concerned specific aspects of parental practices in child-based sporting activities. There is a lack of research covering parent-athlete interpersonal relationships concerned with how the relationships affect adolescent prosocial behavior. The purpose of this mixed methods explanatory sequential study was to examine teenage athletes' prosocial behavior and their relationships with parents. To achieve our purpose, we obtained quantitative data from 1348 athletes and non-athletes (ages 12-16), and qualitative data from 12 adolescent athletes and 12 youth sports parents. In the quantitative phase, we assessed adolescent prosocial behavior regarding the following six forms of prosocial behavior: public, anonymous, dire, compliant, altruistic and emotional. In the qualitative follow-up, three themes emerged from the adolescent athlete's perspective: (1) sport as an escape; (2) parent-child relationships in youth sports; (3) adolescents' desired behavior. Three themes emerged from the parental perspective: (1) sport as protection and as a school of life; (2) painful decisions to release a child; (3) understanding adolescent behavior. We found protection from delinquent behavior and increased prosocial behavior with securely attached young athletes who are actively involved in sports.